Interdisciplinary care of pediatric oncology patients: A survey of clinicians in Central America and the Caribbean. Issue 5 (14th February 2023) - Graetz, Dylan E.; Chen, Yichen; Devidas, Meenakshi; Antillon‐Klussmann, Federico; Fu, Ligia; Quintero, Karina; Fuentes‐Alabi, Soad L.; Gassant, Pascale Y.; Kaye, Erica C.; Baker, Justin N.; Rodriguez Galindo, Carlos; Mack, Jennifer W.
Abstract: Background: Quality cancer care depends on interdisciplinary communication. This study explored the communication practices of interdisciplinary clinicians, the types of healthcare services for which they engage in interdisciplinary collaboration, and the association between interdisciplinary care and perceived quality of care, as well as job satisfaction. Methods: We conducted a survey of interdisciplinary clinicians from cancer centers in Guatemala, Honduras, Panama, El Salvador, and Haiti. The survey included 68 items including previously validated tools and novel questions. Results: Total 174 interdisciplinary clinicians completed the survey: nurses ( n  = 60), medical subspecialists ( n  = 35), oncologists ( n  = 22), psychosocial providers ( n  = 20), surgeons ( n  = 12), pathologists ( n  = 9), radiologists ( n  = 9), and radiation oncologists ( n  = 5). Oncologists reported daily communication with nurses (95%) and other oncologists (91%). While 90% of nurses reported daily communication with other nurses, only 66% reported daily communication with oncologists, and more than 50% of nurses reported never talking to pathologists, radiologists, radiation oncologists, or surgeons. Most clinicians described interdisciplinary establishment of cancer treatment goals and prognosis (84%), patient preferences (81%), and determination of first treatment modality (80%). Clinicians who described more interdisciplinary collaboration had higher job satisfaction ( p  = .04) and perceived a higher level of overall quality of care ( p  = .004). Conclusions: Clinicians in these limited resource settings describe strong interdisciplinary collaboration contributing to higher job satisfaction and perceived quality of care. However, nurses in these settings reported more limited interdisciplinary communication and care. Additional studies are necessary to further define clinical roles on interdisciplinary care teams and their associations with patient outcomes.